Factors associated with appropriate and low-value PSA testing. (June 2020) - Oswald, Nathaniel; Lin, Tengda; Haaland, Benjamin; Flynn, Michael; Kawamoto, Kensaku; Cooney, Kathleen A.; Lowrance, William; Hanson, Heidi A.; O'Neil, Brock
Highlights: Low-value PSA testing is most likely among patients with prior PSA values. Men 55–65 year old are most likely to receive low-value PSA testing. Urologist are most likely among providers to order low-value PSA testing. Abstract: Background: Prostate-specific antigen (PSA) testing for early detection of prostate cancer is low-value when it is not indicated by guidelines and the harms outweigh the benefits. In this retrospective cohort study, we identify provider and patient factors associated with PSA testing, particularly in situations where testing would be low-value. Methods: We used electronic health record data from 2011 to 2018 representing 1, 738, 021 health system encounters in the United States. Using logistic generalized estimating equation models, we examined patient factors (age, comorbid illness, family history, race and prior PSA results), provider factors (gender, specialty, graduation year and medical school rank), and overall time trends associated with PSA testing in low-value and appropriate settings. Results: Comorbid illness (odds ratio (OR) 0.0 for 3+ conditions vs none) and no prior PSA testing (OR 0.2) were associated with a lower likelihood of PSA testing in low-value situations, while family history of prostate cancer (OR 1.6) and high prior PSA test results (OR 2.2 for PSA > 6 vs 0–1) were associated with a greater likelihood. Men aged 55–65 years were at greatest risk for PSA testing in low-value situations. The provider factor associated with PSA testing in low-value situations was specialty, with urologists being most likely (OR 2.3 versus advanced practice providers). Internal medicine physicians were more likely to perform PSA testing during low-value situations (OR 1.3 versus advanced practice providers) but much more likely to order a PSA test where appropriate (OR 2.2). All PSA testing decreased since 2011. Conclusion: We identified several patient and provider factors associated with PSA testing in low-value settings. Some aspects suggest attention to relevant factors for PSA testing in low-value settings (e.g. comorbid illness), while others may encourage PSA testing in low-value settings (e.g. family history). The greatest likelihood of PSA testing in low-value settings is among men within the age range most commonly recommended by guidelines.